2013
DOI: 10.5713/ajas.2012.12652
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Constituents of Rabbits Subjected to Transportation under Hot, Humid Tropical Conditions

Abstract: Unlike Europe (particularly, Italy and Spain), where a number of studies have been conducted on the stressful effects of transport on rabbit welfare, few studies have been conducted on transportation of rabbits under hot, humid tropical conditions experienced in countries like Malaysia. We studied the effects of transportation in hot humid tropical conditions of Malaysia on physiometabolic changes in New Zealand white rabbits. Eighty experimental animals were divided into two groups of 40 bucks each and transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…In this study, the glucose increased following road transport, probably in relation to glycogenolysis and gluconeogenesis associated with the increase in catecholamine and glucocorticoids during stressful conditions (Shaw and Tume, 1992;Mazzone et al, 2010). This glucose increase could be also due to involvement of glucose in energy metabolism during transport inducing a mobilisation of body energy reserve and resulting in its quantification as a useful tool for assessing stress (Warriss, 2010;Nakyinsige et al, 2013). According to previous works (Choe and Kim, 2014), the results of this study showed that animals with high blood glucose levels also had high blood lactate levels.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…In this study, the glucose increased following road transport, probably in relation to glycogenolysis and gluconeogenesis associated with the increase in catecholamine and glucocorticoids during stressful conditions (Shaw and Tume, 1992;Mazzone et al, 2010). This glucose increase could be also due to involvement of glucose in energy metabolism during transport inducing a mobilisation of body energy reserve and resulting in its quantification as a useful tool for assessing stress (Warriss, 2010;Nakyinsige et al, 2013). According to previous works (Choe and Kim, 2014), the results of this study showed that animals with high blood glucose levels also had high blood lactate levels.…”
Section: Discussionmentioning
confidence: 75%
“…As for glucose levels, the pattern of lactate concentration has been characterised by a significant increase after the road transport and a consequent decrease to basal values that we can interpret as part of the physiological response to a stressor. For example, when the circulating system permits working of muscle with adequate oxygen, a shift to anaerobic oxidation with consequent increment in blood lactate concentration occurs (Nakyinsige et al, 2013). In addition, PCV increased significantly after the road transport and this is in contrast with Mazzone et al (2010) and Liste et al (2008), who did not find any variation of PCV in rabbits after a short transport.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations